The role of naming sponsors in summer music festivals - Andrade, Serenela Alves de (2018)
The present dissertation was performed to understand the connection between branding and summer Portuguese music festivals, in order to recognize the role that the first has been having in the second, due to their increasing impact. More precisely, the objective is to study several variables related to the consumer behaviour and the necessary communication marketing needs that should exist for a successful concretization of the event and which steps naming sponsors need to follow, due to the actual circumstances of the national panorama. This research is looking to understand how the responsible for the main Portuguese music festivals are currently aware of the importance that a naming sponsor has for the success and performance of festivals and also, the opinion of the festival goers about them and their role in contributing for future improvements on services and infrastructures. At the end and after performing in-depth interviews and a netnography, it seems that naming sponsors are important for the edification of each edition but in general, they don’t influence the desire to go to a festival. Its excessive presence is justified as inefficient and injurious for certain services and functionalities. The challenge is improving quality in festivals without massively showing the presence of naming sponsors and also provide subtle options for retention of the festival goers.